The malaise of social experience and its impact on academic engagement among young students in Kabylia - SAOUD, Tarek (Journal of Human Sciences, 2022)
The university environment has become today for young student a considerable source of social malaise. In spite of the many and various sporting, cultural, intellectual… activities present that can allow them to flourish and integrate into the university’s world, it turns out that these young people express rather reluctance towards it, which is expressed clearly in their speeches. The objective of this article is to highlight the main points of a study we conducted among young university students of Tizi Ouzou, Bejaia and Bouira to identify the main factors that feed this malaise gaining more and more of these young students and its effects on their academic engagement.